Arsitektur Masjid Jami' “Sunan Dalem” Gresik Tahun 1500-2000 - Novi Dwi Andriani; Imam Ibnu Hajar (Qurthuba: The Journal of History and Islamic Civilization, 2021)
Abstract: The article entitled "History of the Structure and Architecture of the Jami Mosque" "Sunan Dalem" Gumeno Village, Manyar District, Gresik Regency, 1500-2000 "the formulation of the problem in this study is: 1) What are the Geographical and Demographic Conditions of Gumeno Village, Manyar District, Gresik Regency; 2) What is the Architectural Style of the Jami' Sunan Dalem Mosque Today; 3) What is the history of the development of the Jami' Sunan Dalem Mosque, Gumeno Village, Manyar District, Gresik Regency. This article was written using historical research methods with the following steps: heuristics (data collection), verification (data criticism), interpretation (data interpretation) and historiography (historical writing). This writing uses a historical and anthropological approach. Historically to look at the history of the establishment of the mosque from the various architectural changes that have occurred in it from year to year by looking at the chronological and anthropological sequence of events or events which are very relevant because of anthropology, the incessant curiosity about humans in their cultural system, namely as the heir of a a complex system of customs, attitudes and behavior. This writing also uses the Structural theory of Jean Peaget and Ibn Khaldun regarding the development of History (Ashabiyah). From the results of the study, it can be concluded that: That Gumeno Village is located on the coast, the architecture of the Jami' Sunan Dalem Mosque today follows the traditional architectural style and development has 4 periods, namely the initial stage of rehabilitation, the second stage of changing the pillars of the teacher, the third stage of the restoration of building material elements, the third stage the four additions to the decoration of the Gumeno Mosque. Keywords: history, anthropology, architecture